Meningitis due to Salmonella in preterm neonates - Totan, Mehmet; Küçüködük, Şükrü; Dağdemir, Ayhan; Dilber, Cengiz (The Turkish Journal of Pediatrics, 2002)
Meningitis due to Salmonella is a rare condition. Here we report seven cases with neonatal Salmonella meningitis diagnosed and treated in the Pediatric Neonatology Unit of Ondokuz Mayıs University Faculty of Medicine between January 1985-February 2001. Five cases were cured with appropriate treatment; in two of them no neurological sequelae were seen. Of the remaining three, reversible hydrocephalus occurred in two cases and subdural empyema was found in one. Two patients died on the 30th and 40th days of hospitalization: one of them had hydrocephalus and the other ventriculitis. In this report we point out the importance of neonatal meningitis due to Salmonella serotypes, though it rarely occurs.
Keywords: Salmonella; meningitis; newborn